Strategi Digital dan Affiliate Marketing terhadap Keputusan Pembelian Gen Z: Studi Kasus Produk Antarestar di TikTok Shop - Muflif, Dika Nabil; Pratiwi, Ni Made Ida; Mulyati, Awin (STAI Denpasar Bali, 2025)
This study aims to examine the influence of Digital Marketing and Affiliate Marketing on the purchasing decisions of Antarestar products on TikTok Shop among Generation Z in Surabaya. The research method employed is a quantitative approach using questionnaires distributed via Google Forms to collect data from respondents. The population in this study consists of Generation Z individuals in Surabaya who have used Antarestar products. A total of 30 respondents were selected using purposive sampling. Data were analyzed and hypotheses tested using SPSS version 22. The results of the partial test (t-test) reveal the following findings: (1) Digital Marketing has a significant influence on the purchasing decisions of Antarestar products on TikTok Shop, indicating that the presence of Antarestar on the platform tends to increase purchase decisions among Gen Z consumers in Surabaya; (2) Affiliate Marketing also significantly influences purchase decisions, suggesting that promotional efforts through affiliates positively impact consumer decisions. (3) Furthermore, the simultaneous test (F-test) shows that Digital Marketing and Affiliate Marketing together have a significant impact on purchasing decisions. These findings indicate that Digital Marketing can help build brand awareness and initial interest, while Affiliate Marketing can enhance consumer trust through recommendations and reviews by affiliates. Therefore, both Digital Marketing and Affiliate Marketing are crucial variables that Antarestar should prioritize to achieve better marketing outcomes. Keywords: Digital Marketing, Affiliate Marketing, Purchasing Decision